Assessment of the Nutritional Status, Bone Mineralization, and Anthropometrics of Children with Thalassemia Major - Serap Cevher Bulğurcu; Aylin Canbolat Ayhan; Hamdi Cihan Emeksiz; Fahri Ovalı (Medeniyet Medical Journal)
Objective: Children with thalassemia major (TM) are prone to growth failure and micronutrient deficiency. Thus, this study aimed to evaluate nutritional status, anthropometrics, and bone mineralization defects in patients with regular blood transfusion. Methods: Data obtained were analyzed by evaluating laboratory tests, anthropometric measures, and bone mineral density. Results: This study included 29 patients (62% male and 38% female) with a mean age of 12.26±4.74 years, mean pre-transfusion hemoglobin of 8.64±1.01 g/dL, and mean serum ferritin of 1158.6±556.8 ng/ mL. Vitamin D (72.4%), selenium (72.4%), and folate (37.9%) deficiencies were most frequent. Hypocalcemia was observed in 17.2%, hypomagnesemia in 3.5%, and decreased ceruloplasmin in 10.3% of patients. Folate was higher between 2 and 6 years old (p=0.028). Ceruloplasmin was higher between 6 and 10 years old (p=0.018). Selenium was significantly higher in patients with a ferritin of ≥1,500 (p=0.008). No significant ferritin-related differences were found in other micronutrients (p>0.05). Body mass index (BMI) were <5 percentile (p) in 31% of patient, whereas none was >95 p. Height in 24.5% and weight in 20.7% of patients were <3 p, whereas none with >97 p. BMI of patients aged 10-18 years was significantly higher (p=0.001). Anthropometric percentiles did not significantly differ in the mean serum ferritin and micronutrient levels. Hypoparathyroidism was observed in 13.8% and hypothyroidism in 3.5% of patients. Low bone density was detected in 14.8% (2 osteopenic and 2 osteoporotic) of patients. Bone mineral density did not significantly differ in the ferritin and micronutrient levels. Conclusions: Nutritional support and deficiency prevention are important to minimize the burden of complications and increase the life expectancy and quality in patients with TM.